2019
DOI: 10.14710/nmjn.v9i2.26435
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Manual Handling Training and Lifting Devices on Risks of Back Pain among Nurses: An Integrative Literature Review

Abstract: Background: Musculoskeletal injuries, notably lower back injuries, are major occupational health problems among nurses. These injuries occur mainly due to incorrect use of body mechanics upon handling, lifting, and transfer of patients. It is the leading cause of occupational disability and is associated with increased healthcare costs. Reducing these injuries can lead to a significant reduction in healthcare costs.Purpose: This integrative literature review aims to examine the impacts of manual handling and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In an integrative review of the impact of patient handling training and lift devices on nurse back pain, the authors found multiple lift devices and trainings, that incorporated ergonomics, body mechanics and posturing did prevent and lessen back pain (Aljohani & Pascua, 2019). This review also identified barriers to these interventions that included: safety climate within an organisation, availability of the equipment, individual nurse experiences and knowledge, and sustained use of techniques and equipment over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an integrative review of the impact of patient handling training and lift devices on nurse back pain, the authors found multiple lift devices and trainings, that incorporated ergonomics, body mechanics and posturing did prevent and lessen back pain (Aljohani & Pascua, 2019). This review also identified barriers to these interventions that included: safety climate within an organisation, availability of the equipment, individual nurse experiences and knowledge, and sustained use of techniques and equipment over time.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of interventions to prevent and reduce musculoskeletal injuries among nurses found that the most common types of interventions were patient lift systems, patient handling training and multi‐component interventions although overall studies in this review lacked high quality evidence (Richardson et al, 2018). In an integrative review of the impact of patient handling training and lift devices on nurse back pain, the authors found multiple lift devices and trainings, that incorporated ergonomics, body mechanics and posturing did prevent and lessen back pain (Aljohani & Pascua, 2019). This review also identified barriers to these interventions that included: safety climate within an organisation, availability of the equipment, individual nurse experiences and knowledge, and sustained use of techniques and equipment over time.…”
Section: Discussionmentioning
confidence: 99%
“…In Chapter X, Article 86 of Law No. 13 (McCullagh, 2012). The OHN nurse is prepared for various specialist positions.…”
Section: A Government Policymentioning
confidence: 99%
“…Manual lifting is considered to be an assistive motion for sit-to-stand. Posture adjustment based on ergonomics has been found to be effective for reducing lumbar load during manual lifting [ 4 ]. Trunk angle and foot position have been considered important posture parameters for reducing the lumbar load during manual lifting [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%